2022
DOI: 10.1097/md.0000000000028313
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between double-plate fixation and posterior plate fixation for comminuted olecranon fracture using two triceps screws in synthetic bone model

Abstract: Background: Although preventing triceps fragment displacement is essential for treating an olecranon fracture, we frequently encounter situations in which only a few screws can be fixed to the triceps fragment. The aim of this study was to compare the stability of double-plate fixation and posterior plate fixation for olecranon fractures when the triceps fragment was small and only 2 screws could be inserted. Methods: A composite ulna model was used to simulate olecrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Those studies suggested that risk of failure is higher with osteoporotic bone and when the fracture is proximal to the midpoint of sigmoid notch. The use of 2 proximal triceps screws and augmentation with SR or TBW might be beneficial in more proximal fractures [51][52][53][54][55][56][57][58][59][60][61][62] (Fig. 6).…”
Section: Plate Osteosynthesismentioning
confidence: 99%
“…Those studies suggested that risk of failure is higher with osteoporotic bone and when the fracture is proximal to the midpoint of sigmoid notch. The use of 2 proximal triceps screws and augmentation with SR or TBW might be beneficial in more proximal fractures [51][52][53][54][55][56][57][58][59][60][61][62] (Fig. 6).…”
Section: Plate Osteosynthesismentioning
confidence: 99%